Rates of short-GRB afterglows in association with binary neutron star mergers. Issue 1 (1st December 2017) - Saleem, M; Pai, Archana; Misra, Kuntal; Resmi, L; Arun, K G
Abstract: Assuming all binary neutron star (BNS) mergers produce short gamma-ray bursts, we combine the merger rates of BNS from population synthesis studies, the sensitivities of advanced gravitational wave (GW) interferometer networks, and of the electromagnetic (EM) facilities in various wavebands, to compute the detection rate of associated afterglows in these bands. Using the inclination angle measured from GWs as a proxy for the viewing angle and assuming a uniform distribution of jet opening angle between 3° and 30°, we generate light curves of the counterparts using the open access afterglow hydrodynamics package boxfit for X-ray, optical, and radio bands. For different EM detectors, we obtain the fraction of EM counterparts detectable in these three bands by imposing appropriate detection thresholds. In association with BNS mergers detected by five (three) detector networks of advanced GW interferometers, assuming a BNS merger rate of 0.6–774 Gpc −3  yr −1 from population synthesis models, we find the afterglow detection rates (per year) to be 0.04–53 (0.02–27), 0.03–36 (0.01–19), and 0.04–47 (0.02–25) in the X-ray, optical, and radio bands, respectively. Our rates represent maximum possible detections for the given BNS rate since we ignore effects of cadence and field of view in EM follow-up observations.